Intermediate algebra - Larson, Ron.; David E. Heyd (Canada : D. C Heath and Company, 1992)
It contains all of the material that is in the student text. Intermediate algebra has two basic goals: First, to help students develop proficiency in algebra; and second, to show students how algebra can be used as a modeling language for real-life problems.
Chapter1. Introduction to algebra -- Chapter2. Linear equations and inequalities -- Chapter3. Polynomials and factoring -- Chapter4. Rational expressions -- Chapter5. Radicals and complex numbers -- Chapter6. Quadratic equations and inequalities -- Chapter7. Introduction to analytic geometry -- Chapter8. Functions and mathematical models -- Chapter9. Systems of equation and inequalities -- Chapter10. Exponential and logarithmic functions -- Chapter11. Additional topics in algebra .
Includes index.
Keywords: ALGEBRA